TREATMENT OF GOSSIPIBOMA – AN EXPERIENCE OF 20 CASES - Muhammad Jamil; Rashid Usman; Muhammad Afzal (Journal of University Medical & Dental College, 2017)
ABSTRACT OBJECTIVES: To share personal operative experience of patients with gossipiboma in terms of clinical presentation, diagnosis, treatment, outcome and preventive measures to minimize the incidence with review of relevant literature. STUDY DESIGN: retrospective study PLACE AND DURATION: Multiple army hospitals since Jan1995 to Sep2015. PATIENTS AND METHODS: The study includes collective personal surgical experience of two vascular surgeons, one general surgeon, one orthopaedic surgeon and one chest surgeon, with patients of gossipiboma. The data of 20 patients was collected and analysed. The literature was searched for current information. RESULTS: Male and female were 5 and 15 respectively. The mean age was 33 years ranging from 16 to 53 years. Gossipiboma found in patients after Caesarean section (08), hysterectomies (04), thoracotomy (02), appendectomy (01) mastectomy (01), thigh abscess (01), throidectomy (01), shoulder surgery (01) and arteriovenou fistula(01). In almost 16 cases abdominal sponge and in 04 cases surgical gauze were removed. Ultrasonography and CT scan were the investigations used to help in diagnosis. All patients recovered after removal of gossipiboma. CONCLUSION: Retained surgical sponge is a medical error occurring inadvertently commonly in obstetrical emergency procedures. CT scan is the investigation of choice for diagnosis. Correct counting thrice, x-rays of the involved area, use of bar coding of sponge, use of radioactive identification chip system and training of the operating room staff can minimize this error.